Local adaptation and colonization are potential factors affecting sexual competitiveness and mating choice in Anopheles coluzzii populations - Charles Nignan; Bèwadéyir Serge Poda; Simon Péguédwindé Sawadogo; Hamidou Maïga; Kounbobr Roch Dabiré; Olivier Gnankine; Frédéric Tripet; Olivier Roux; Abdoulaye Diabaté (Scientific Reports, 2022)
Abstract The mating behaviour of the malaria vector Anopheles gambiae complex is an important aspect of its reproduction biology. The success of mosquito release programmes based on genetic control of malaria crucially depends on competitive mating between both laboratory-reared and wild individuals, and populations from different localities. It is known that intrinsic and extrinsic factors can influence the mating success. This study addressed some of the knowledge gaps about factors influcencing mosquito mating success. In semi-field conditions, the study compared the mating success of three laboratory-reared and wild allopatric An. coluzzii populations originating from ecologically different locations in Burkina Faso. Overall, it was found that colonization reduced the mating competitiveness of both males and females compared to that of wild type individuals. More importly, females were more likely to mate with males of their own population of origin, be it wild or colonised, suggesting that local adaptation affected mate choice. The observations of mating behaviour of colonized and local wild populations revealed that subtle differences in behaviour lead to significant levels of population-specific mating. This is the first study to highlight the importance of local adaptation in the mating success, thereby highlighting the importance of using local strains for mass-rearing and release of An. coluzzii in vector control programmes.